Penerapan Metode Pembelajaran CIRC Pada Kemampuan Membaca Pemahaman Siswa Sekolah Dasar - Husna Lailatul latifa; Haryadi Haryadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The low level of students' reading ability has an impact on students' difficulty in understanding reading. The current phenomenon of students' reading comprehension is still low. Basically, students have difficulty understanding the content of the reading such as: 1) students have difficulty in answering questions. 2) students find it difficult to find the main idea. 3) students find it difficult to make a summary of the text read. This study explains the results of the application of the CIRC learning method to students' reading comprehension skills. This research uses qualitative methods obtained from literature studies. According to a literature review from relevant journals, it was obtained that the application of the CIRC method succeeded in improving students' reading comprehension skills in elementary school. Keywords: CIRC method, reading comprehension ability